Results of Laparotomy and Laparoscopy for Perforated Colonic Diverticulitis - An, Sung Bak (JSLS, 2019)
BACKGROUND AND OBJECTIVES: The applications of laparoscopic surgery are expanding, but there is still controversy about its application in patients with peritonitis resulting from diverticulitis perforation. This study aimed to investigate the factors affecting the postoperative mortality rate in patients undergoing surgery for perforated diverticulitis. Further, we compared the recovery courses of patients between open and laparoscopic surgeries. METHODS: We analyzed the medical records of adult patients with peritonitis caused by perforated diverticulitis from six hospitals of Hallym University Medical Center from January 2006 to December 2016. RESULTS: A total of 166 patients were identified. In the univariate analysis, the statistically significant factors associated with postoperative mortality were age ≥ 60 years, body mass index ≥ 23 kg/m(2), American Society of Anesthesiologists score ≥ 3, hypertension, serum blood urea nitrogen ≥ 23 mg/dL, creatinine ≥ 1.2 mg/dL, albumin < 3.0 g/dL, modified Hinchey score ≥ grade III, formation of stoma, and laparoscopic surgery. In multivariate analysis, serum albumin < 3.0 g/dL was the only factor associated with mortality. After case-control matching, we compared postoperative hospital course and prognosis between open and laparoscopic surgery groups. There was no significant difference in the clinical course between the groups. No significant difference was observed in the complication rate, reoperation rate, readmission rate, and mortality. CONCLUSION: Low preoperative serum albumin level (<3.0 g/dL) affects the mortality rate of patients after surgery. The hospital course and prognosis after laparoscopic surgery and conventional open surgery are comparable in patients with peritonitis caused by diverticulitis perforation.